2019
DOI: 10.1051/0004-6361/201834530
|View full text |Cite
|
Sign up to set email alerts
|

A spectral stacking analysis to search for faint outflow signatures inz∼ 6 quasars

Abstract: Aims. Outflows in quasars during the early epochs of galaxy evolution are an important part of the feedback mechanisms potentially affecting the evolution of the host galaxy. However, systematic observations of outflows are only now becoming possible with the advent of sensitive mm telescopes. In this study we use spectral stacking methods to search for faint high velocity outflow signal in a sample of [C ii] detected, z ∼ 6 quasars. Methods. We search for broad emission line signatures from high-velocity outf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 84 publications
(118 reference statements)
2
44
0
Order By: Relevance
“…The stacked cube also suggests that these quasar-driven outflows have extensions of several kpc. Stacking analyses no doubt miss a significant fraction of faint outflows due to orientation effects (Stanley et al 2019), so these results should be considered conservative lower limits.…”
Section: Neutral Atomic Gas Componentmentioning
confidence: 99%
“…The stacked cube also suggests that these quasar-driven outflows have extensions of several kpc. Stacking analyses no doubt miss a significant fraction of faint outflows due to orientation effects (Stanley et al 2019), so these results should be considered conservative lower limits.…”
Section: Neutral Atomic Gas Componentmentioning
confidence: 99%
“…The fluxes were calibrated using the standard flux calibrator P allas, while SDSS J2253+1608 was used as both the phase calibrator and the bandpass calibrator. The typical calibration uncertainty is < 5% in ALMA band 4, here we use 15% uncertainty that also includes the uncertainties of the old P allas flux model in early casa versions (Stanley et al 2019).…”
Section: Almamentioning
confidence: 99%
“…Bischetti et al (2019) studied 48 quasars at 4.5 < z < 7.1 and found broad [C ii] wings that are interpreted to trace outflowing gas with velocities v ∼ > 1,000 km s −1 , an extent of ∼ > 5 kpc, and a deduced a mass outflow rate of order ∼100 M yr −1 . On the other hand, Stanley et al (2019) found only marginal evidence (<3σ) for such outflow signatures in their analysis of 26 z ∼ 6 quasars (the outflow signatures may be more prominent in a subset of about half of these quasars).…”
Section: Outflowsmentioning
confidence: 93%